2019
DOI: 10.1039/c9ra03848e
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated glutamate induced ROS production by antioxidative compounds in neural cell lines

Abstract: Glutamate is an excitatory neurotransmitter involved in neural function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Glutamate levels are the highest immediately after TBI, and these heightened levels are sustained for 24-48 h due to the disruption of the BBB [75]. In addition, there is some evidence that glutamate promotes ROS production [76,77].…”
Section: Excitotoxicitymentioning
confidence: 99%
“…Glutamate levels are the highest immediately after TBI, and these heightened levels are sustained for 24-48 h due to the disruption of the BBB [75]. In addition, there is some evidence that glutamate promotes ROS production [76,77].…”
Section: Excitotoxicitymentioning
confidence: 99%
“…The excitotoxic neurotransmitter glutamate caused neurotoxicity by inducing the overproduction of ROS and subsequently increasing oxidative stress. 51 Previous studies showed that the extracellular glutamate content of MCAO rats reached the highest level in 1–2 hours, and began to decrease after 3 h. 52 The increase in the glutamate content was one of the earliest changes in cerebral ischemia, which was also accompanied by the decreasing amounts of glutamine. 53,54 The results of the present study showed that the serum levels of glutamate and glutamine decreased concurrently 24 h after MCAO, which was consistent with the reported results in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Glutamate is a well-known excitatory neurotransmitter engaged in neural function. Excessive buildup of intercellular glutamate leads to increased concentrations of ROS and RNS in neuronal cells [ 49 ]. Activation of the NMDA receptor by glutamate application to cultured forebrain neurons stimulates a localized ROS formation.…”
Section: Role Of Ros Generated In the Neuronal Environmentmentioning
confidence: 99%